Lexico-Semantic and Stylistic Features of Diplomatic Correspondence (On the Example of English and Uzbek Languages) - Mirzamatova Ziyoda Abdullaevna; Mukhiddinova Khadicha Sobirovna (Genius Journals, 2021)
This study examines the texts of modern English-language diplomatic correspondence; the subject is the lexical and semantic features of the texts of diplomatic correspondence. The lexical and semantic features of diplomatic correspondence are highlighted, the main translation transformations in the translation of English-language texts of diplomatic correspondence into Uzbek are considered
Keywords: Diplomatic Correspondence; Lexical and Semantic Features; Translation Transformations; Stylistic Features